MANAJEMEN SOSIALISASI KEGIATAN PESANTREN VIA INSTAGRAM DI PESANTREN MODERN ZIIS CILONGOK - Ichwan Hero Handriyanto; Novan Ardy Wiyani (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to analyze the socialization management of pesantren activities through the Instagram platform at ZIIS Cilongok Modern Islamic Boarding School. The method used in this research is qualitative with a case study approach. The time of the research was conducted during the period March 1 to March 25, 2023. The objects of research included the Director of the ZIIS Cilongok Modern Islamic Boarding School, the ZIIS Cilongok Modern Islamic Boarding School Asatidz board, and the Instagram admin of the ZIIS Cilongok Modern Islamic Boarding School. Data collection techniques used in this study include interviews, observation, and documentation. The collected data will be analyzed using data triangulation techniques to gain a more comprehensive understanding of the socialization management of pesantren activities through Instagram. The results of this study indicate that in planning the socialization management of Islamic boarding schools activities through Instagram, it is important to use an attractive template that is in accordance with the identity of the Islamic boarding school. In addition, the use of a high-quality camera is also an important factor in producing interesting content. In terms of organization, it is important to form a special team that is responsible for managing Islamic boarding schools' Instagram accounts and creating clear job descriptions. In implementation, the Instagram account management team made templates and uploaded all existing activities so that people could access information about the daily activities of the santri more easily. The school principal also plays a role in supervising and controlling content uploaded via Instagram ZIIS. In the evaluation, a meeting was held with the Media Team to further develop the Islamic boarding school's Instagram account. In addition, a question column was created in the Story to provide opportunities for viewers and santri guardians to provide input and responses to content uploaded on Instagram ZIIS.